Exponential of Sum/Real Numbers/Proof 5
Jump to navigation
Jump to search
Theorem
Let $x, y \in \R$ be real numbers.
Let $\exp x$ be the exponential of $x$.
Then:
- $\map \exp {x + y} = \paren {\exp x} \paren {\exp y}$
Proof
This proof assumes the definition of $\exp$ as a series.
Then:
\(\ds \map \exp {x + y}\) | \(=\) | \(\ds \sum_{n \mathop = 0}^\infty \frac 1 {n!} \paren {x + y}^n\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{n \mathop = 0}^\infty \frac 1 {n!} \sum_{k \mathop = 0}^n \frac {n!} {k! \paren {n - k}!} x^k y^{n - k}\) | Binomial Theorem | |||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{n \mathop = 0}^\infty \sum_{k \mathop = 0}^n \paren {\frac 1 {k!} x^k} \paren {\frac 1 {\paren {n - k}!} y^{n - k} }\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \paren {\sum_{n \mathop = 0}^\infty \frac {x^n} {n!} } \paren {\sum_{n \mathop = 0}^\infty \frac {y^n} {n!} }\) | Definition of Cauchy Product | |||||||||||
\(\ds \) | \(=\) | \(\ds \map \exp x \, \map \exp y\) |
$\blacksquare$